Age determination of Magallanes (MAG) peat core from Patagonia - Roland, Thomas P (PANGAEA, 2021)
14C and 210Pb age determination of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland